Psychomotricity as a predictive skill for the literacy process - Moi , Raysa Soares; Paz, Cláudia Terra do Nascimento (Seven Editora, 2024)
The study aims to investigate the importance of psychomotricity for the literacy process as a fundamental factor for the development of the child’s cognitive, physical, emotional and social aspects. Through playful activities, children, in addition to having fun, create, interpret and interact with the world in which they live, considering the relationship between movement and learning, and the disharmony between them can be harmful to the child. Literacy is a complex process that involves skills, and among them are motor skills. In educational institutions, the greatest difficulties faced by teachers and students are in the process of acquiring reading and writing, and in cognitive development, where minimum conditions are necessary that constitute, among others, the structure of psychomotor education. Psychomotricity in the literacy process is fundamental for the construction of several concepts that serve as pillars in the learning process, and within its specific areas, it offers many intervention options so that children of literacy age can overcome any obstacles and achieve the proposed objectives and goals. The methodology consists of a systematic literature review, with the objective of finding the main researches related to the referred theme, using for data collection the main scientific networks of academic search in the area of education, such as, Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (CAPES), in the Brazilian Digital Library of Theses and Dissertations of the Brazilian Institute of Information in Science and Technology (IBICT), Scielo Digital Portal and Google Scholar Portal, which resulted in ten papers addressing the subject of interest. However, after applying the inclusion/exclusion criteria, only six studies were listed to support a critical study on the literacy process and its relationship with Psychomotricity. As a result, the studies indicate that it is essential to introduce the psychomotricity theme in the classes planned for the routines of school institutions and the knowledge of teachers regarding the theme, in order to apply it correctly in their classes. DOI:https://doi.org/10.56238/sevened2023.008-025